Media education and use of technological resources in Ibero-American classrooms - Arciniega Cáceres, Mittzy (2019)
Abstract. The present article aims to present a reflection, within the Ibero-American context, on the use of digital resources in the classroom and its relationship with media education to highlight common points and diverse strategies in addressing both aspects in education systems, as well as to establish the main challenges for a real media education that could take advantage of new technologies in the classroom. The methodology used for this purpose is mainly based on a systematic review of the literature on the subject performed between the years 2012 and 2018. Moreover, the article addresses some of the results of the “Citizen’s media competencies in emerging digital media in university environments” project (2016-2019) from the National Research, Development and Innovation (I+D+I) Plan of the Spanish Government. Additionally, it presents reflections from experts in media competency of the Euro-American inter-university research network Alfamed. The main conclusions include specific initiatives and particular experiences, but they do not imply an integral and innovative use of information and communication technologies. Beyond the inequality in access opportunities, Ibero-American countries make instrumental use of technological resources in the classroom and their potential is not used for a real media education based on innovation in methodologies that could address the challenges that current education system is facing. This article, more than providing new results, entails a systematization and a comparative framework on the evolution, innovative experiences and current situation of the use of technologies in education in different Ibero-American countries.